PENCEGAHAN DAN PENANGANAN KEKERASAN PADA ANAK DI KABUPATEN SAMPANG MELALUI PROGRAM CEKATAN - Christiana, Elisa; Haris H, Ernia; Ferdina, Cucun Setya; Nugrahani, Cantika Iva; Jufrianto, M.; Furqon, Muhammad (LPPM Universitas Bina Bangsa, 2024)
The CEKATAN Program (Preventing Sexual Violence Against Children) represents a comprehensive initiative between Madura State Polytechnic and, the Department of Social Services, Women's Empowerment, and Child Protection of Sampang Regency. This program emphasizes community involvement to optimize efforts in preventing sexual violence against children. The objectives of this initiative include identifying trends in child abuse, gathering cross-sectoral information related to child violence, providing support to child protection workers (PPA) in each district, and reporting cases to promote a